Integrated Problem-Solving in Developing the Skills of State Madrasah Tsanawiyah Principals in Jambi Province - Audra Ayu Bagascary; Mukhtar Mukhtar; Wahyudi Wahyudi (Edumaspul: Jurnal Pendidikan, 2024)
Madrasah Tsanawiyah principals in Jambi Province face a unique set of challenges in balancing academic achievements with the moral and religious education of students. While traditional leadership development programs often focus on technical management skills, they overlook the need for integrated problem-solving strategies that address the multifaceted issues these principals encounter. This research explores how integrated problem-solving can enhance the leadership skills of Madrasah Tsanawiyah principals in Jambi, aligning their leadership practices with both the academic and moral responsibilities of their roles. The study employs a qualitative approach, involving semi-structured interviews, observations, and document analysis to understand the leadership challenges and strategies used by principals. Findings indicate that integrated problem-solving improves decision-making, fosters a culture of continuous improvement, and enhances both interpersonal and strategic leadership skills. Moreover, by incorporating Islamic values, principals are better equipped to manage diverse student populations and improve school performance in a way that aligns with the moral mission of Madrasah Tsanawiyah. This research proposes a framework for integrating problem-solving into leadership development programs, offering a practical solution to the challenges faced by Madrasah principals in Jambi Province.